2023
DOI: 10.1590/1516-3180.2022.0141.r1.17082022
|View full text |Cite
|
Sign up to set email alerts
|

Are sociodemographic and anthropometric variables effective in screening probable and confirmed sarcopenia in community-dwelling older adults? A cross-sectional study

Abstract: BACKGROUND: Screening for probable and confirmed sarcopenia using sociodemographic and anthropometric indicators can be a practical, cheap, and effective strategy to identify and treat older people susceptible to this condition. OBJECTIVES: To identify cutoff points for sociodemographic and anthropometric variables in screening probable and confirmed sarcopenia in community-dwelling older adults. DESIGN AND SETTING: This was a cross-sectional study of community-dwelling older adults in Araranguá, Santa Catarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
3
4
0
Order By: Relevance
“…Thus, divergences in the prevalence of probable sarcopenia across studies may also be related to the socioeconomic conditions of the populations studied. Notably, previous research by our group identified cutoff points for sociodemographic and anthropometric variables in screening for probable and confirmed sarcopenia in community-dwelling older adults [34]. In addition, Kim and Won (2019) found a high prevalence of confirmed sarcopenia in older Korean women (14.4%) when using 5XSST + ASM, which is in line with the present results (27.5%) [35].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, divergences in the prevalence of probable sarcopenia across studies may also be related to the socioeconomic conditions of the populations studied. Notably, previous research by our group identified cutoff points for sociodemographic and anthropometric variables in screening for probable and confirmed sarcopenia in community-dwelling older adults [34]. In addition, Kim and Won (2019) found a high prevalence of confirmed sarcopenia in older Korean women (14.4%) when using 5XSST + ASM, which is in line with the present results (27.5%) [35].…”
Section: Discussionsupporting
confidence: 92%
“…This result suggested that high WC and BF were significantly related to a lower incidence of sarcopenia ( 47 ). Moreover, the sarcopenia classification from an anthropometric method showed that WC was useful in screening for possible sarcopenia ( 48 ). This result supported our study, which considered the strong association of WC with the anthropometric method to predict possible sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, since studies have shown that sarcopenia is associated with age and BMI 27,28 ,we adjusted for these two variables. Secondly, lifestyle factors, socioeconomic factors, individual history of diseases and total energy intake can also in uence the association between AAJ and sarcopenia [29][30][31] . Thus, we subsequently adjusted for smoking status, drinking status, PA, education level, household income, diabetes, hypertension, hyperlipidemia, coronary heart disease, depressive symptoms score and total energy intake.…”
Section: Discussionmentioning
confidence: 99%